Modelling the growth of popliteal artery aneurysms. Issue 13 (23rd August 2018) - Shiwani, H; Baxter, P; Taylor, E; Bailey, M A; Scott, D J A
Abstract: Background: Popliteal artery aneurysms (PAAs) comprise up to 85 per cent of all peripheral aneurysms. Few longitudinal studies track their progression. This study aimed to track the growth of asymptomatic PAAs in a hospital-based ultrasound service, and compare models of aneurysm growth. Methods: This retrospective single-centre cohort study included patients who had a PAA on arterial duplex ultrasound imaging of the lower limbs between 1 January 2011 and 1 January 2016. Progression of PAA size and progression to event or intervention were the primary outcome measures. Results: Some 282 images were analysed: 47 limbs with PAA were included in a cohort of 32 patients (15 had bilateral PAAs). Twenty patients also had an abdominal aortic aneurysm (AAA). Linear multilevel modelling estimated that PAA growth was 2·4 (95 per cent c.i. 1·6 to 3·7) mm a year. Growth was estimated at 0·8 (0·1 to 1·5) mm per year in patients without an AAA and 3·5 (2·9 to 4·2) mm per year in those with a known AAA (previous open repair, previous endovascular aneurysm repair or AAA under surveillance) ( P < 0·001). Conclusion: Growth rates of PAA were heterogeneous but were optimally predicted by multilevel modelling. Patients with an existing AAA may have faster PAA progression than those without. Abstract : Non-linear